La percezione veneziana dello Stato Ottomano. Dalla presa di Costantinopoli al dopo Lepanto (1453-1574) - Cimarosti, Maurizio (Ledizioni, 2021)
For centuries the Most Serene Republic of Venice and the Ottoman State danced between war and peace, between the desire for expansion and domination and mutual commercial and diplomatic needs. The book covers 120 years of history, including the rise and fall of two political and military realities that characterised the 15th and 16th centuries, but it does so above all "through the eyes" of the protagonists and those contemporary with the events. The "image of the Turk" is therefore conveyed mainly through the use of primary sources (often still unexplored or rarely published) and embraces many aspects: not only conflicts and battle narratives, but also cultural, religious, economic and artistic aspects. The book touches on the different fields of interaction between Westerners, especially Venetians, and Ottomans, analysing the elements of contrast, but also of proximity and mutual fusion and influence, in an attempt to reconstruct events and atmospheres around these two great states, structuring History as a compelling and unpredictable novel.